Prevention and Eradication of Corruption With Information and Communication Technology Progress - Anshar, Anshar Al Kamil; Kennan, Kennan Arbain Nur; Rafif, Rafif Reyhan (Dinasti Research, 2020)
This research aims to provide several ways that can be done by the Indonesian government on how to use the development of information technology that is now available and especially in the Republic of Indonesia. The data presented in this research journal can be used as a reference as a way to eradicate corruption, and can help the government in eradicating the disease that has undermined the Indonesian State, namely corruption or fraud. Corruption is one of the causes for the inadequate use of state revenues, which can be in the form of taxes, PNBP, customs etc. So that indirectly it can affect the development process in Indonesia, where the source of funds for the construction of public facilities, health and education comes from Indonesia's state revenue. This study uses an approach based on quantitative analysis methods with survey results based on data on the daily life of Indonesians in various circles of society carried out by various survey bodies or institutions in various countries that remain focused on the use of technology in Indonesia so that contrasting ideas can arise. which can shed some light on those who care about this country to fight for their rights which are taken away by the corruptors and other rats of the country. The use of technology can not only be used to prevent acts of corruption but can also be done in eradicating it, this is possible because the development of this information technology has reached a government system where everything someone does must have digital traces left such as corruption. This study uses a data presentation method with descriptions, charts and survey results.